Implementation of a system for documentary procedures in public institutions applying Robotic Process Automation (RPA) - Ramirez, Christian Flores (2023)
The research has shown that, in Peru, public institutions have a deficient service in document management, as a result, it generates loss of time, accumulation and low security of documents, which affects citizens. Therefore, this paper proposes to implement RPA technology through a web system, which has been developed, as objective of automating the workflow and avoiding performing repetitive tasks. This technological solution will generate great improvements for public institutions such as the reduction of the attention time for a procedure in order to prevent the dissatisfaction of citizens. The proposed solution is verified through evaluations based on the indicators presented. Finally, a considerable improvement was shown in the procedures, improving the experience of citizens and workers by reducing the attention time from 516 minutes to 490 minutes on average, which implies a saving of approximately 26 minutes, but it should be noted that the attention time for a procedure may vary depending on the type of procedure.